Respuesta :
Answer:
Option A)
[tex]9x^2 - 36x + 35 = 0[/tex]
Step-by-step explanation:
We are given the following in the question:
Roots of quadratic equation are:
[tex]\alpha = \dfrac{5}{3}, \beta = \dfrac{7}{3}[/tex]
The sum of the roots and the product of the roots can be calculated as:
[tex]\alpha + \beta = \dfrac{5+7}{3} = 4\\\\\alpha\beta = \dfrac{5}{3}\times \dfrac{7}{3} = \dfrac{5}{9}[/tex]
Standard form of quadratic equation:
[tex]x^2-(\alpha + \beta)x+\alpha\beta = 0[/tex]
Putting values, we get,
[tex]x^2 - 4x + \dfrac{35}{9} = 0\\\\9x^2 - 36x + 35 = 0[/tex]
is the required quadratic equation.
Thus, the correct answer is
Option A)
[tex]9x^2 - 36x + 35 = 0[/tex]
Answer:
A) 9x^2 − 36x + 35 =0
Step-by-step explanation:
9x^2 − 36x = −35
Using the zero-product property, write the solutions as factors of the quadratic equation and multiply:
(x − 5/3)(x − 7/3) = 0
9x2 − 36x + 35 = 0
9x2 − 36x = −35